Elimination of raindrops effects in infrared sensitive camera - Abdullah, Ahmad Sharmi (2007)
Surveillance systems are important part of the security systems nowadays. The traditional methods of surveillance systems involving human now have improved to automated systems. The effects of rain brought some drawback to the automated surveillance systems especially during rainy night time which degrade the performance of the tracking system. This project has proposed a method to eliminate those raindrops effects in order to improve the performance of the tracking system in the automated surveillance systems. An algorithm has been developed using MATLABÂ® Image Processing Toolbox. Unique visual properties of raindrops are observed and analyzed which then has been manipulated into the algorithm as a mechanism for raindrops effects removal. The result produced as a comparison to its original input shows a significant raindrops effects elimination.